Sexual Violence during World War II in Polish Academic Historiography. Remarks on the Margin of Joanna Ostrowska’s Book - Kolbuszewska, Jolanta (Sensus Historiae, 2019)
The pretext for writing this article was Joanna Ostrowska’s book Przemilczane. Seksualna praca przymusowa w czasie II wojny światowej published in 2018 by Publishing House Marginesy. The publication was devoted to the phenomenon (repressed from the collective memory) of sexual exploitation of Polish women in institutions controlled by the German occupier. However, the author did not limit herself to World War II, she also took into account the post-war lot of victims, their stigmatization, the repression and tabooing of the phenomenon of occupational prostitution. Ostrowska’s book is the first attempt in Polish historiography to tackle the phenomenon of Polish women’s wartime sexual trauma. In addition to presenting an interesting book, Jolanta Kolbuszewska wonders why Polish historiography has delayed taking up the subject for so long. In trying to answer this question, she considers two perspectives: the image of the Second War in collective memory and academic historical reflection referring to it.